Factors Affecting the Slenderness Limit for RC Columns-The Use of the (ACI-318M-05) Provisions - Ihsan A. S. Al-Sharrbaf (مجلة النهرين للعلوم الهندسية, 2008)
The current ACI code and many other codes permit the moment magnification method for design of slender reinforced concrete (RC) columns. Manually, the design/analysis procedure is tedious, so that the codes state a pre-prediction if the column is slender or not. In other words, before starting design codes